Four years of emergency surgery. Emergency Service Experience of the Pasteur Hospital - Montano, Daniel; Castro, Teresa; Curi, Jorge (Cirugía del Uruguay, 1999)
Service of Emergency of the Pasteur Hospital in the tour years understood between April 1 of 1993 and March 31 of 1997. The resu/ts were ana!yzed fundamental/y in which ít refer to the surgical activity of the residents and the teaching of the surgery. We evidenced that a resident of surgery formed in the Pasteur Hospital, operate less than 50 patients of urgency per year. We conc!uded that in spite of that it is continua!ly a tapie of discussion of the uruguayan congresses of surgery, it has not been the road in arder to increase and improve the leve/ of practica/ teaching of the young surgeon.